From classrooms to conservation: scaling environmental education across India’s Western Ghats - Karanth, Krithi K.; Unnikrishnan, Sruthi; Salazar, Gabby (Frontiers in Conservation Science, 2025)
Biodiversity hotspots are areas of exceptional ecological value and they often coincide with high human population densities. These biodiverse areas may experience high levels of human-wildlife conflict, threatening both wildlife and local communities. While environmental education (EE) offers a promising tool for mitigating conflict, the ecological, cultural, and political diversity across hotspots poses significant challenges for designing and adapting effective EE interventions. To test whether an EE program could scale across the Western Ghats, a biodiversity hotspot in India, we developed and implemented the Wild Shaale program in government schools across three states: Goa, Karnataka and Tamil Nadu from June 2022 to February 2023. Our objective was to assess whether the program had a consistent impact across states or if regional differences influenced learning outcomes. Here, we report on data from 7381 students from 200 schools around 11 wildlife reserves with equal participation from boys and girls across the three states. We found that participation in the Wild Shaale program led to significant increases in environmental knowledge and knowledge of safety behaviors in all three states, as well as small positive shifts in most measures of environmental attitudes. We also found that there are significant differences in baseline attitudes towards wildlife and baseline levels of environmental knowledge across states. Students in Karnataka and Tamil Nadu had a more positive baseline attitude towards wildlife in general compared to Goa and students in Tamil Nadu had the lowest pre-test scores on environmental knowledge questions. Despite small regional differences, we found that Wild Shaale emerges as a scalable education program that is effective across diverse cultural, political and ecological contexts. We show that a single, adaptable EE program can be effectively scaled across diverse socio-ecological contexts.